Fatigue Life Evaluation of Racks for the Three Gorges Ship Lift Based on the Load Spectrum - Chen Zhuo; Shi Lubing; Yan Xiaoqing; Tang Weibi; Li Xuefei; Liu Zhongming (Jixie chuandong)
Aiming at the problem that the rack and pinion for the Three Gorges ship lift may face fatigue failure during its whole life cycle, the load spectrum including the stressed tooth surface and the number of load cycles is constructed in this study based on the rack and pinion load calculated by the torques of the driving motors and the synchronous shafts. Combined with the S-N curve of racks and Miner's linear cumulative damage criterion, the damage degree and residual fatigue life of racks within 35 years of design life are calculated. In addition, the cumulative iteration method is used to calculate the contact and bending safety factors of the rack, which realizes the comparison between the actual load and the design load of the rack and the operation safety performance verification. The results show that, the upper tooth surface of the rack has more meshing times, and its probability is 73.03%. During the design life, the total contact fatigue damage degree of the upper tooth surface of the rack is 1.65×10-12, and the total number of cycles according to the load spectrum is 1.87×1017. The total damage degree of the bending fatigue of the upper tooth surface of the rack is 8.15×10-14; the total number of cycles according to the load spectrum is 3.78×1018; the rack has a long residual fatigue life after 35 years of design life. The contact safety factor of the racks SH=2.958, bending safety factor SF=8.106, are both greater than the selected minimum safety factor under high reliability and the calculated safety factor under design load, and the safety margin of ship lift racks is sufficient. The research content of this study has enriched the relevant research in the field of fatigue life of super-large modulus racks and pinions, and provides theoretical basis and data support for the operation and maintenance of the Three Gorges ship lift.